Teachers’ and Learners’ Perceptions of Streaming Learners and Their Impact on the Teaching and Learning of Principles of Accounts at Ordinary Level in Masvingo Urban District Secondary Schools - Mandina, Shadreck (Advances in Social Sciences Research Journal, 2015)
This study set out to find out the perceptions of teachers and learners of Principles of Accounts at ordinary (“O”) level in Masvingo Urban District secondary schools in Masvingo Province in Zimbabwe regarding streaming of learners and how such perceptions impact on the teaching and learning of the subject. The descriptive survey design was adopted for this study because it enabled the researchers to study a limited number of cases with a view of drawing up conclusions about the generality of the whole group under study. The estimated population of the study was eight (8) “O” level Principles of Accounts teachers, eight hundred and forty (840) “O” level Principles of Accounts students in four (4) schools in Masvingo Urban District and two (2) education inspectors of commercial subjects in the same district. A sample of one hundred and eight (108) learners and six (6) teachers from three (3) schools and the two education inspectors was used in the study. Data were collected through the use of questionnaires, interviews and observations and then subjected to interpretational analysis. The main findings were that schools streamed students in order to improve the pass rate in the subject, help learners feel better about themselves and to help teachers to be more effective in teaching the subject. However, most learners indicated that they do not like streaming for various reasons. Teachers used different methods to teach learners in different streams. Teachers also made better preparations for lessons that they taught to the fast streams. The academic gains in the fast streams were slight compared with the academic losses in the slow tracks. The researchers recommend continuous monitoring of the academic performance of learners so that can be moved from the fast stream to the slow track and the other way round. The attitudes of teachers towards slow learners in the subject need to be changed through staff development workshops and in service training. Schools are also urged to consider mixed ability grouping which enables cooperative learning to take place. Furthermore, schools are urged to consider setting learners instead of streaming them. Setting involves assigning learners to learning groups on the basis of performance in specific subjects. Teaching and learning resources must be equitably provided to fast and slow tracks where streaming is practised. Schools should also allocate teachers to both streams equitably, that is, slow learners must have their fair share of skilled and experienced teachers.